From Lab to Production: Event Series on Insights into Process Chemistry - Urs Brändli; Jan Cvengros; Stefan Hildbrand; Niklaus Künzle; Maurus Marty (CHIMIA)
As process chemistry is rarely included in university curricula, experts from Swiss companies pass on their experience to students at various levels.